2011
DOI: 10.1128/cvi.00354-10
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal IgA Responses in Healthy Adult Volunteers following Intranasal Spray Delivery of a Live Attenuated Measles Vaccine

Abstract: Measles remains an important cause of morbidity and mortality among children in the developing world. The goal of this study was to examine measles virus-specific mucosal immune responses in healthy immune (n ‫؍‬ 24; plaque reduction neutralization [PRN] titers of >200 mIU/ml) and nonimmune (n ‫؍‬ 24) young adult volunteers who received the monovalent Moraten measles vaccine via intranasal (spray delivery) or subcutaneous immunization. Serum, oral fluid, and nasal wash samples were examined for measles virus-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Remarkably, both recombinant MV-SARS vectors also induced SARS-CoV specific IgA, whereas the subunit reference vaccine did not. This raises an interesting point since several clinical studies already evidenced that parenteral administration of live attenuated measles vaccine to children stimulates secretory IgA responses in nasal washes (Bellanti et al, 2004;Simon et al, 2011). Although we did not assess the ability of recombinant MV-SARS to induce secretory IgA in the lungs and upper respiratory tract of immunized mice, this result is strongly indicative of the potential of MV-SARS to induce SARS-CoV specific secretory IgA responses.…”
Section: Discussionmentioning
confidence: 76%
“…Remarkably, both recombinant MV-SARS vectors also induced SARS-CoV specific IgA, whereas the subunit reference vaccine did not. This raises an interesting point since several clinical studies already evidenced that parenteral administration of live attenuated measles vaccine to children stimulates secretory IgA responses in nasal washes (Bellanti et al, 2004;Simon et al, 2011). Although we did not assess the ability of recombinant MV-SARS to induce secretory IgA in the lungs and upper respiratory tract of immunized mice, this result is strongly indicative of the potential of MV-SARS to induce SARS-CoV specific secretory IgA responses.…”
Section: Discussionmentioning
confidence: 76%
“…For example, the median neutralizing antibody titer for our cohort was 844 mIU/ml (interquartile range: 418–1752; minimal value: 45; maximal value: 7723) 7.4 years after two doses of MMR vaccine, and the median IFN-γ ELISPOT response was 36 (interquartile range: 13–69; minimal value: −17; maximal value: 208) IFN-γ-positive spot-forming units (SFUs) per 200,000 cells, suggesting substantial biological variability, waning immunity and potential susceptibility to measles [17,22]. Our research team [23] and others [2426,203] have called for maintenance of and/or progress toward measles elimination, recognizing the related challenges, including the need for research on determinants of measles vaccine response, and the development of improved measles vaccines.…”
Section: Re-emergence Of Measles Current Vaccine Limitations and Next-mentioning
confidence: 99%
“…57 Many published studies have shown that nasally administered vaccines induce serum IgG and mucosal IgA that are important for deliberating enhanced efficacy of vaccine. 57,58 The enhanced induction of mucosal IgA antibodies has been shown to play a significant role in neutralizing pathogens such as Streptococcus pneumonia 59 and measles viruses 60 and preventing further infection. Moreover, intranasal immunization has also been reported to induce cross-reactive antibodies that might be indicative of cross-protection.…”
Section: Advantages Of Nasal Vaccine Deliverymentioning
confidence: 99%